2013
DOI: 10.1002/jsfa.6018
|View full text |Cite
|
Sign up to set email alerts
|

Changes in fatty acid profile of feta cheese including conjugated linoleic acid

Abstract: CLA content significantly increased during the ripening stages and decreased during aging (P ≤ 0.05). CLA is not stable during manufacture and storage of feta cheese, a fact which should be resolved, since this biologically active substance can be obtained from the diet.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

10
17
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(31 citation statements)
references
References 40 publications
10
17
0
Order By: Relevance
“…These results were also in agreement with those obtained by [31] for the transfer of C18:1 and C18:2 FA isomers from ewe's milk to Peccorino Toscano cheese. In addition, several authors [12,31,32] found that C18:2 cis-9, trans-11 isomer increased between 10% and 26% on total content of CLA during ripening of different cheeses, which is also compatible with our results. This CLA increase has been associated to hydrogen donors in processed cheese [33].…”
Section: Resultssupporting
confidence: 93%
See 1 more Smart Citation
“…These results were also in agreement with those obtained by [31] for the transfer of C18:1 and C18:2 FA isomers from ewe's milk to Peccorino Toscano cheese. In addition, several authors [12,31,32] found that C18:2 cis-9, trans-11 isomer increased between 10% and 26% on total content of CLA during ripening of different cheeses, which is also compatible with our results. This CLA increase has been associated to hydrogen donors in processed cheese [33].…”
Section: Resultssupporting
confidence: 93%
“…The ratio omega-6/omega-3 increased (p<0.05) throughout the ripening in cheeses manufactured from milk with a low CLA content, and remained unchanged for medium CLA contents. These interactions have not been studied up to now and would explain some discrepancies about the CLA evolution over ripening found by several authors [12,31,32,34].…”
Section: Resultsmentioning
confidence: 95%
“…In that study, SFA increased after 37 days of ageing and decreased thereafter, while MUFA and PUFA showed the opposite tendency (Laskaridis et al . ).…”
Section: Resultsmentioning
confidence: 97%
“…Besides, Laskaridis et al . () reported that the CLA content of feta cheese decreased during 42 days of storage.…”
Section: Resultsmentioning
confidence: 97%
“…Afterwards, they are transported as free fatty acids to the liver where they are metabolized via mitochondrial β-oxidation without triglycerides resynthesize, acting as a quick energy source for cells. Furthermore, these short-chain fatty acids also play an interesting role on the sensory characteristics of cheeses due to their lower perception thresholds in comparison to longer-chain fatty acids (Laskaridis et al, 2013).…”
Section: Cheese Fatty Acid Contentmentioning
confidence: 99%